EFEKTIVITAS FOTOREDUKSI ION Cu(II) TERKATALISIS TiO2 DALAM LIMBAH CAIR INDUSTRI KERAJINAN PERAK DI DESA UNGGA KEC. PRAYA LOMBOK TENGAH - Husnul Hatimah, Husnul Hatimah (Hydrogen: Jurnal Kependidikan Kimia, 2017)
This research has been done to study the effect of addition of TiO2 photocatalyst in liquid waste of silver industry in Ungga Village, Kec. Praya Kab. Central Lombok on the effectiveness of photoreduction of Cu (II) ions which are catalyzed by TiO2. The photoreduction process is carried out by irradiating liquid waste containing Cu (II) ions without or with the addition of TiO2 photocatalyst powder in a closed reactor equipped with UV lamps. The photoreduction process conditions are 50 mL of silver waste containing Cu (II) with reaction time for 24 hours and a mass of TiO2 20 mg at each 10 ppm Cu (II) ion concentration. The photoreduction results are determined by the difference in the concentration of the starting Cu (II) ions with the residual Cu (II) ion concentration in the silver craft waste without or with the addition of TiO2 photocatalyst. Furthermore, the data obtained were compared to the results of photoreduction of Cu (II) ions pure TiO2 laboratory scale. The amount of metal in the mixture was determined by Atomic Absorption Spectrophotometric Method (AAS). The results showed that in silver handicraft waste containing Cu (II) ions, the addition of TiO2 can increase the effectiveness of the Cu (II) ion photoreduction from 6.57% to 33.38%, which begins with the adsorption process. The other ions cause inter-reduction competition metals so as to decrease the effectiveness of TiO2 catalysed Ti (II) ionic ferrication in silver handicrafts waste in Ungga Village Kec. Praya Kab.central Lombok